THE IMPACT OF CSR TOWARDS FIRM VALUE WITH FINANCIAL PERFORMANCE AS INTERVENING VARIABLE (Empirical Study of Companies Listed in LQ45 of IDX for the period 2017-2019) - Jaunanda, Meiliana; Jonathan, Bryan (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2024)
This research was conducted to (1) Analyze the impact of CSR towards Return on Assets; (2) Analyze the impact of CSR towards Price-to-Book Value; (3) Analyze the impact of Return on Assets to Price-to-Book Value; (4) Analyze the impact of CSR towards Price-to-Book Value with Return on Assets as intervening variable. The independent variable CSR is divided into 6 categories which include CSR Economy, CSR Environment, CSR Employee Practices, CSR Human Resources, CSR Community, and CSR Product Responsibility. The populations in this study are the companies in the LQ45 Index listed on the Indonesian Stock Exchange between 2019-2021. Purposive sampling was used with a total sample of 31 companies which have published financial reports and sustainability reports in all years of 2019-2021. Data were analyzed using multiple linear regression method. The results showed that (1) CSR Employee Practices has a negative significant impact on Return on Assets, and CSR Product Responsibility has positive significant impact on Return on Assets; (2) CSR Employee Practices has a negative significant impact on Price-to-Book Value, CSR Human Rights has a positive significant impact on Price-to-Book Value, and CSR Product Responsibility has positive significant impact on Price-to-Book Value; (3) Return on Assets have a positive and significant impact towards Price-to-Book Value; (4) CSR Product Responsibility has positive significant impact on Price-to-Book Value, Return on Assets have a positive significant impact towards Price-to-Book Value.